HEART ATTACK (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
A heart attack,or myocardial infarction, occurs when blood flow to a part of the heart is obstructed, typically due to atherosclerosis —a buildup of plaque in coronary arteries. This blockage deprives cardiac muscle of oxygen, leading to tissue damage.Symptoms often include chest pain or discomfort, radiating pain in the arms, neck, jaw, or back, shortness of breath, and nausea. Immediate recognition of these signs is crucial for timely intervention. The American Heart Association emphasizes the importance of calling emergency services at the first sign of a heart attack.Risk factors  include hypertension, hyperlipidemia, smoking, diabetes, obesity, and a sedentary lifestyle. Preventive measures involve lifestyle modifications such as a balanced diet rich in fruits, vegetables, whole grains, and lean proteins, regular physical activity, and smoking cessation.In the event of a heart attack, treatmentsmay include medications like antiplatelets (e.g., aspirin), thrombolytics to dissolve clots, and procedures such as angioplasty and stent placement. Long-term management may involve cardiac rehabilitation and lifestyle changes to reduce the risk of future events.